Soil and soil fertility management research in Sub-Saharan Africa : fifty years of shifting visions and chequered achievements /: fifty years of shifting visions and chequered achievements. (2017) - Mutsaers, H. J. W, 1940-; Coyne, Danny; Hauser, Stefan; Huising, Jeroen; Kamara, Alpha; Nziguheba, Generose; Pypers, Pieter; Taulya, Godfrey; van Asten, Piet; Vanlauwe, Bernard
No abstract available